Vital signs and other observations used to detect deterioration in pregnant women: an analysis of vital sign charts in consultant-led UK maternity units. (May 2017) - Smith, G.B.; Isaacs, R.; Andrews, L.; Wee, M.Y.K.; van Teijlingen, E.; Bick, D.E.; Hundley, V.; ,
Highlights: Early warning systems used in UK consultant-led maternity units vary considerably. Many different vital sign ranges are used to define normal maternal physiology. Research is required to inform the normal vital sign ranges expected during pregnancy. Obstetric early warning systems and charts should be standardised. Abstract: Background: Obstetric early warning systems are recommended for monitoring hospitalised pregnant and postnatal women. We decided to compare: (i) vital sign values used to define physiological normality; (ii) symptoms and signs used to escalate care; (iii) type of chart used; and (iv) presence of explicit instructions for escalating care. Methods: One-hundred-and-twenty obstetric early warning charts and escalation protocols were obtained from consultant-led maternity units in the UK and Channel Islands. These data were extracted: values used to determine normality for each maternal vital sign; chart colour-coding; instructions following early warning system triggering; other criteria used as triggers. Results: There was considerable variation in the charts, warning systems and escalation protocols. Of 120 charts, 89.2% used colour; 69.2% used colour-coded escalation systems. Forty-one (34.2%) systems required the calculation of weighted scores. Seventy-five discrete combinations of 'normal' vital sign ranges were found, the most common being: heart rate=50–99 beats/min; respiratory rate=11–20 breaths/min; blood pressure, systolic=100–149 mmHg, diastolic ≤89 mmHg; SpO2 =95–100%; temperature=36.0–37.9°C; and Alert-Voice-Pain-Unresponsive assessment=Alert. Most charts (90.8%) provided instructions about who to contact following triggering, but only 41.7% gave instructions about subsequent observation frequency. Conclusion: The wide range of 'normal' vital sign values in different systems suggests a lack of equity in the processes for detecting deterioration and escalating care in hospitalised pregnant and postnatal women. Agreement regarding 'normal' vital sign ranges is urgently required and would assist the development of a standardised obstetric early warning system and chart.